Unmasking the Many Faces of Giloy (Tinospora cordifolia L.): A Fresh Look on its Phytochemical and Medicinal Properties - Verma, Deepak K.; G., Kimmy; Kumar, Pradyuman; El-Shazly, Mohamed (Current Pharmaceutical Design, 2021)
Background: Plants have been used to treat health disorders and prevent diseases since antiquity in all civilizations including the Indian and Chinse. Giloy (Tinospora cordifolia L.) is one of the most important medicinal plants in Indian folk medicine and is commonly known as the “Heart-leaved Moonseed” or “Guduchi”. Giloy is a perennial shrubby creeper of the Menispermaceae family. It is native to the tropical areas of India, Sri Lanka, Myanmar, Sothern Eastern Asia, Africa, and Australia. It attracted attention in the last few decades because its roots, stems, and leaves are used in folk medicine treating several disorders. Methods: To reveal its potential, we reviewed the literature on this plant over the last five decades using several search engines. Results: Giloy is recommended in diabetes, stomachache, jaundice, urinary problems, skin ailments, and prolonged diarrhea and dysentery. The medicinal properties of T. cordifolia extracts were attributed to its phytochemical content including steroids, alkaloids, diterpenoid lactones, and glycosides. Conclusion: In this review, we summarized the phytochemical content of T. cordifolia and its medicinal properties with special emphasis on its antioxidant, anti-inflammatory, and cytotoxic activities. We aimed to provide natural product researchers with a full picture of the potential applications of this plant in the development of food additives and nutraceuticals.
Keywords: Menispermaceae